Public support for carbon taxes varies across countries and policy design must consider the national context - Hamid Bulut; Robin Samuel (Communications Earth & Environment)
Abstract Although carbon taxes are an effective way for countries to meet the emissions targets set out in the Paris Agreement, these policies remain unpopular. Here we present a survey experiment conducted in China, Germany, India, and the UK, based on over 13,000 evaluations of policy designs. We examined four factors influencing public support: effectiveness in reducing emissions, impact on household costs, use of tax revenues, and international coordination. Communicating environmental effectiveness increased support, while making costs explicit reduced it. Preferences for revenue use varied: some respondents favoured direct payments, while others preferred investments in welfare. Contrary to expectations, only German respondents showed increased support when other countries also adopted similar measures. These findings highlight the importance of national context in shaping public attitudes. Carefully designed and clearly communicated carbon tax policies can improve public acceptability and enhance the political feasibility of effective climate action.